STRATEGI PEREMPUAN MISKIN DALAM MEMPERTAHANKAN KELANGSUNGAN HIDUP - Benjamin, Benjamin (JURNAL SOSIOLOGI, 2013)
Writing the results of this study aims to explain about Strategies In Retaining Women Poor Survival in Urban District of the Cape of Good to Labuan in Dublin in 2010 . Study informants took five women / mothers or widows ditingal her husband died of Poor Households where the theree informants poor women of Lingkungan I and two informants poor women of the Lingkungan II . The method used is descriptive qualitative . Data collection techniques used , namely in-depth interviews and documentary studies . Based on the results of this study concluded that the strategy of poor women in maintaining the viability of all the ability to find a solution that is done in an effort to meet the needs of family life . Here the survival strategy or by pressing dicukup insufficiency , especially in subsistence daily meals . Generally they are the spirit of working hard as a laundry worker , factory workers , artisans and trade marung sequence. Dependence on assistance from other parties or other persons who may otherwise still expected as first aid given by the government Raskin and BLT . To meet the needs of school education strategy her children , because they are trying to prioritize for the future . Although low income , they do not work any more with the term odd jobs working with pattern holes dug hole covered.